Invitro antioxidant, h+k+atpase inhibitory activity of traditional antiulcer herbs - K.RAJASEKAR; K.GAYATHRI (International Journal of Pharma and Bio Sciences, 2016)
Globally available folklore medicines are consumed by people as food, without scientific validation. Aim of the present study is to evaluate the antiulcer and antioxidant activity of traditional herbs. Physicochemical analysis, preliminary phytochemical analysis and quantitative analysis of aerial parts from Solanum nigrum and Cynodon dactylon were carried out. the free radical scavenging activity of aqueous extracts of both herbs was carried out by adopting different assays. Antiulcer activity of both extracts was evaluated by H+K+ ATP ase inhibitory activity. Results of the present study reveal that the collected herb was pure, nutritionally rich in nature. IC50 values reveal that aqueous extract from Solanum nigrum is a potent inhibitor of lipid peroxidation than Cynodon dactylon (p<0.05). Reducing potential,free radical scavenging activity and H+K+ ATP ase inhibitory activity of both extracts did not differ significantly. To conclude, both herbs are equally potent antioxidants and proton pump inhibitors.